Induced Sputum for the Diagnosis of Pulmonary Tuberculosis: Is It Useful in Clinical Practice? - S-R Olsen; R Long; GJ Tyrrell; D Kunimoto (Canadian Respiratory Journal)
BACKGROUND: Diagnosing pulmonary tuberculosis (PTB) is challenging in patients who are unable to spontaneously expectorate. Published evidence suggests that induced sputum (IS) is the least invasive and most cost-effective method of diagnosis, and should be used before fibre-optic bronchoscopy (FOB).